Learner-based Teaching (Resource Books for Teachers) - Campbell C.; Kryszewska H.; Maley A. (Oxford Oxford University Press, 1995)
This book includes 70 language practice activities that make use of the wealth of knowledge, experience, and expertise that students bring to the classroom.
Keywords: 811.111